Electroacupuncture for stress-predominant mixed urinary incontinence: a protocol for a three-armed randomised controlled trial - Yan Yan (BMJ Publishing Group, 2021)
Introduction Evidence specific for stress-predominant mixed urinary incontinence is still lacking at present, and acupuncture may relieve the symptoms. We plan to conduct this multi-centre, three-armed, randomised controlled trial to investigate the efficacy and safety of electroacupuncture among women with stress-predominant mixed urinary incontinence.Methods and analysis The trial will be conducted at five hospitals in China. Two hundred thirty-two eligible women will be randomly assigned (2:1:1) to the electroacupuncture, sham electroacupuncture or waiting-list group to receive either 24-session acupuncture/sham acupuncture treatment over 8 weeks and 24-week follow-up or 20-week watchful waiting. The primary outcome is the proportion of participants with at least 50% reduction in mean 24-hour stress incontinence episode frequencies from baseline to week 8. The outcome will be analysed with the intention to treatpopulation (defined as participants randomised) with a two-sided p value of less than 0.05 considered significant.Ethics and dissemination The protocol has been approved by Guang’anmen Hospital Institutional Review Board (2019-241-KY). Detailed information of the trial will be informed to the participants, and written informed consent will be obtained from every participant. Results of the trial are expected to be published in a peer-reviewed journal.Trial registration number ClinicalTrials.gov Registry (NCT04299932).